Peran Bhabinkamtibmas Cegah Curanmor - Andre Hastary (Police Studies Review, 2020)
The purpose of this study was to determine the role of Bhabinkamtibmas in the context of preventing criminal acts of theft of two-wheeled motor vehicles in the jurisdiction of Depok Police Station. This study uses a qualitative approach with field research methods. Data analysis with data reduction, data presentation, and drawing conclusions. The results showed that the role of Bhabinkamtibmas in the framework of preventing criminal acts of theft of two-wheeled motor vehicles in the jurisdiction of the Depok Police Sector was not yet significant. Efforts made by Depok Police Bhabinkamtibmas in the framework of preventing criminal acts of stealing two-wheeled motor vehicles are guided by Article 16 of the Republic of Indonesia National Police Chief Regulation Number 3 of 2015 concerning Community Policing by promoting the Door to Door System program. The conclusion of this study is that the efforts of Bhabinkamtibmas in the context of overcoming criminal acts of curanmor have been in accordance with the Regulation of the Head of the Indonesian National Police Number 3 of 2015 concerning Community Policing, although it has not been effective. Recommendation. Depok Sector Police are advised to intensify counseling and outreach conducted by Bhabinkamtibmas.